It’s harder than just saying hi: exploring the formation and sustainability of social bonds among first-year university students - Yitong Liu; Wendy Wrapson; Richard Siegert (International Journal of Adolescence and Youth)
Forming and sustaining social connections is integral to university students’ sense of belonging and well-being, yet many face challenges in building meaningful relationships. This study explored these challenges through 20 semi-structured interviews with recent first year students. Using thematic analysis, five key themes emerged: (1) Barriers in forming social connections, (2) Strategies used to connect with other students, (3) Sustaining social bonds, (4) Personality traits impact the cultivation of social networks, and (5) University support to aid social interaction. While participants acknowledged the importance of social connectedness, some expressed indifference or deprioritized forming relationships, citing academic pressures, personal preferences, or limited opportunities for meaningful interaction. Barriers such as pre-existing social groups, cultural and language differences, and hybrid learning environments compounded these challenges. Universities should consider tailoring support programs to better align with students’ evolving preferences and the realities of hybrid educational contexts.